Acceptable time of surgical delay for hip fracture surgery in elderly patients: comparison between American Society of Anaesthesiologists physical status classes I–II versus classes III–IIV - Nalamliang, Arus; Prasopchoke, Narat; Sukapan, Hemmaraj; Pongkunakorn, Anuwat (International Journal of Research in Orthopaedics, 2023)
Background: Elderly patients with high American Society of Anaesthesiologists (ASA) physical status (classes III–IV) have higher reported postoperative mortality for hip fracture. Whether the acceptable time of surgical delay among patients with high ASA scores (classes III–IV) and those with low ASA scores (classes I–II) is different has not been clearly investigated. Methods: A retrospective cohort study was conducted on 2,035 patients aged ≥60 years who underwent hip fracture surgery between January 2005 and December 2020. The 1-year mortality rate was compared between patients with waiting times beyond the indexed day versus those within the indexed day of 1 to 5. The least time point detecting a significant difference was considered the acceptable time of surgical delay. Results: There were 1,099 cases (54.0%) in the high ASA group. In the low ASA group, the 1-year mortality rate was significantly lower than the high ASA group (3.5% versus 6.5%, p=0.003), and patients with a waiting time >4 days had a higher mortality rate than those receiving surgery ≤4 days (5.4% vs. 1.8%, OR 2.98, 95%CI 1.40–6.34, p=0.003). For the high ASA group, patients with a waiting time >2 days had a higher mortality rate than those receiving surgery ≤2 days (7.2% versus 3.1%, OR 2.31, 95% CI 1.01–5.25, p=0.036). Conclusions: The elderly with hip fractures in ASA classes I–II could wait for surgery up to 4 days and 2 days in ASA classes III–IV without a significantly increased 1-year mortality.